Origin and accumulation mechanisms of petroleum in the Carboniferous volcanic rocks of the Kebai Fault zone, Western Junggar Basin, China. (1st September 2016) - Chen, Zhonghong; Zha, Ming; Liu, Keyu; Zhang, Yueqian; Yang, Disheng; Tang, Yong; Wu, Kongyou; Chen, Yong
Highlights: Carboniferous oil in Karamay area is a mixture primarily from P1 f source rock. Three main petroleum chargings occurred from the Middle Triassic to Late Jurassic. High porosity and oil enrichment develop within 150 m of Carboniferous top unconformity. Secondary dissolution pores and fractures are two major reservoir space. Carboniferous top unconformity is crucial pathway in oil lateral migration. Abstract: The Kebai Fault zone of the West Junggar Basin in northwestern China is a unique region to gain insights on the formation of large-scale petroleum reservoirs in volcanic rocks of the western Central Asian Orogenic Belt. Carboniferous volcanic rocks are widespread in the Kebai Fault zone and consist of basalt, basaltic andesite, andesite, tuff, volcanic breccia, sandy conglomerate and metamorphic rocks. The volcanic oil reservoirs are characterized by multiple sources and multi-stage charge and filling history, characteristic of a complex petroleum system. Geochemical analysis of the reservoir oil, hydrocarbon inclusions and source rocks associated with these volcanic rocks was conducted to better constrain the oil source, the petroleum filling history, and the dominant mechanisms controlling the petroleum accumulation. Reservoir oil geochemistry indicates that the oil contained in the Carboniferous volcanic rocks of the Kebai Fault zone is a mixture. The oil is primarily derived from the source rock of the Permian Fengcheng Formation (P1 f ), and secondarily from the Permian Lower Wuerhe Formation (P2 w ). Compared with the P2 w source rock, P1 f exhibits lower values of C19 TT/C23 TT, C19+20 TT/ΣTT, Ts/(Ts + Tm) and ααα-20R sterane C27 /C28 ratios but higher values of TT C23 /C21, HHI, gammacerane/αβ C30 hopane, hopane (20S) C34 /C33, C29 ββ/(ββ + αα), and C29 20S/(20S + 20R) ratios. Three major stages of oil charge occurred in the Carboniferous, in the Middle Triassic, Late Triassic to Early Jurassic, and in the Middle Jurassic to Late Jurassic periods, respectively. Most of the oil charged during the first stage was lost, while moderately and highly mature oils were generated and accumulated during the second and third stages. Oil migration and accumulation in the large-scale stratigraphic reservoir was primarily controlled by the top Carboniferous unconformity with better porosity and high oil enrichment developed near the unconformity. Secondary dissolution pores and fractures are the two major reservoir storage-space types in the reservoirs. Structural highs and reservoirs near the unconformity are two favorable oil accumulation places. The recognition of the large-scale Carboniferous volcanic reservoirs in the Kebai Fault zone and understanding of the associated petroleum accumulation mechanisms provide new insights for exploring various types of volcanic reservoir plays in old volcanic provinces, and will undoubtedly encourage future oil and gas exploration of deeper strata in the region and basins elsewhere with similar settings.